(untitled) (Asian Journal of Medical Sciences, 2024)
Background: Infertility is a prevalent medical issue that can arise from challenges in male or female or both partners. Pivotal contributing factors to female infertility include dysfunction, tubal issues, and peritoneal factors. Hysterosalpingography (HSG) holds significant importance in assessing abnormalities associated with the uterus and fallopian tubes. Aims and Objectives: This study aimed to assess the clinical profile and hysterosalpingographic findings of women with infertility who visited the department of radiodiagnosis for HSG. Materials and Methods: This is a cross-sectional study, where consecutive convenience-based sampling was used, with ethical clearance in place. Sixty-three infertile women of reproductive age were recruited for the study and were referred for HSG by the Department of Obstetrics and Gynecology. Results: The majority of the participants had primary infertility (71.88%) and was in the 31–35-year age group with the majority having 3–6 years of infertility and endometriosis. On HSG uterine pathology was found in 9.37% of participants and unilateral and bilateral tubal blocks were seen in 18.75% and 14.06% of cases approximately. Conclusion: HSG is a minimally invasive procedure, secure, and plays a crucial role in diagnosing uterine and tubal factors contributing to infertility.